2008
DOI: 10.1021/cm801669x
|View full text |Cite
|
Sign up to set email alerts
|

Yellow-Orange-Emitting CaAlSiN3:Ce3+ Phosphor: Structure, Photoluminescence, and Application in White LEDs

Abstract: The crystal structure and photoluminescence properties of undoped and Ce3+-doped CaAlSiN3 as well as the application of white-light LEDs are reported. CaAlSiN3 and CaAlSiN3:Ce3+ have been synthesized, starting from Ca3N2, AlN, Si3N4, and CeN or CeO2 with and without Li3N, by a solid state reaction at 1700 °C for 4 h under high purity nitrogen atmosphere. Instead of an ideal CaAlSiN3, a more appropriate formula is proposed to be CaAl1−4δ/3Si1+δN3 (δ ≈ 0.3−0.4) with an Al/Si ratio of about 1:2 on the basis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
293
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 408 publications
(308 citation statements)
references
References 23 publications
14
293
0
1
Order By: Relevance
“…The value of the bandgap is close to the results published. 10,39 The intense reflection in the visible spectral range is in agreement with the observed gray-white daylight color of undoped CaAlSiN 3 Additionally, the absorption edge of CaAlSiN 3 : Mn 2+ shifts to longer wavelength, corresponding to the decrease in the optical bandgap with increasing Mn 2+ concentration. According to the band and electronic structure calculation results, the bottom of the conduction band (CB) of CaAlSiN 3 is mainly composed of Ca 3d orbitals, and Al/Si 3s/3p orbitals are hybridized at higher energy, while the top of valence band (VB) are dominated by the 2p states of N atoms.…”
Section: Cesupporting
confidence: 82%
See 3 more Smart Citations
“…The value of the bandgap is close to the results published. 10,39 The intense reflection in the visible spectral range is in agreement with the observed gray-white daylight color of undoped CaAlSiN 3 Additionally, the absorption edge of CaAlSiN 3 : Mn 2+ shifts to longer wavelength, corresponding to the decrease in the optical bandgap with increasing Mn 2+ concentration. According to the band and electronic structure calculation results, the bottom of the conduction band (CB) of CaAlSiN 3 is mainly composed of Ca 3d orbitals, and Al/Si 3s/3p orbitals are hybridized at higher energy, while the top of valence band (VB) are dominated by the 2p states of N atoms.…”
Section: Cesupporting
confidence: 82%
“…It was found that Al/Si disorderly occupies the 8b site in the space group of Cmc2 1 with a ratio of about 1/2 with a more appropriate formula CaAl 1-4δ/3 Si 1+δ N 3 (δ = 0.3 -0.4) instead of 1/1 proposed for an ideal CaAlSiN 3 , probably due to the incomplete reaction resulting in a significantly lower Al solubility in CaAlSiN 3 . 10 Thus, a small amount of AlN can be detected for undoped and Mndoped CaAlSiN 3 samples.…”
Section: Cementioning
confidence: 95%
See 2 more Smart Citations
“…Nevertheless there are some indications of stability issues for certain (oxy)nitride compositions [40,134]. For instance, it appeared that (Ca,Sr)AlSiN 3 was more stable [82] against oxidation than M 2 Si 5 N 8 phosphors, the latter showing considerable degradation of the PL intensity when heated to 573K in air, with the stability depending on the stoichiometry [81].…”
Section: Oxynitrides and Nitridesmentioning
confidence: 99%